2021
DOI: 10.1136/bmj.n2288
|View full text |Cite
|
Sign up to set email alerts
|

Female authorship of covid-19 research in manuscripts submitted to 11 biomedical journals: cross sectional study

Abstract: Objective To describe prominent authorship positions held by women and the overall percentage of women co-authoring manuscripts submitted during the covid-19 pandemic compared with the previous two years. Design Cross sectional study. Setting Nine specialist and two large general medical journals. Population Authors of research manuscripts submitted between 1 Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 49 publications
(130 reference statements)
3
52
1
Order By: Relevance
“…24 While another group had also documented disparities in women authorship for COVID-19 research, 37 the analysis of Gayet-Ageron et al specifically found that research about or related to COVID-19 topics resulted in women not holding prominent first and last/senior author positions more often at the beginning of the pandemic compared with during the prepandemic. 24 While it is known that women took on more responsibilities in the early stages of the pandemic (ie, childcare/caretaking, homeschooling, household demands) these reported discrepancies further exacerbate the gender biases and inequalities women face in publication of original research. Despite significant differences in how women and men experience diseases and drug effects, most research and funding has focused on topics and medications that are more relevant to men.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 While another group had also documented disparities in women authorship for COVID-19 research, 37 the analysis of Gayet-Ageron et al specifically found that research about or related to COVID-19 topics resulted in women not holding prominent first and last/senior author positions more often at the beginning of the pandemic compared with during the prepandemic. 24 While it is known that women took on more responsibilities in the early stages of the pandemic (ie, childcare/caretaking, homeschooling, household demands) these reported discrepancies further exacerbate the gender biases and inequalities women face in publication of original research. Despite significant differences in how women and men experience diseases and drug effects, most research and funding has focused on topics and medications that are more relevant to men.…”
Section: Discussionmentioning
confidence: 99%
“…A recent BMJ article by Gayet-Ageron et al analysed women’s authorship position during the COVID-19 pandemic in relation to COVID-19-specific research. 24 While another group had also documented disparities in women authorship for COVID-19 research, 37 the analysis of Gayet-Ageron et al specifically found that research about or related to COVID-19 topics resulted in women not holding prominent first and last/senior author positions more often at the beginning of the pandemic compared with during the prepandemic. 24 While it is known that women took on more responsibilities in the early stages of the pandemic (ie, childcare/caretaking, homeschooling, household demands) these reported discrepancies further exacerbate the gender biases and inequalities women face in publication of original research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, unlike previous studies, we provide a systematic analysis of academic fields. Some scholars have examined very broad areas of knowledge, such as mathematics, physics, or economics [ 13 – 15 ], while others have focused on journals on a very specific topic, such as medicine [ 19 , 20 ] or biological sciences [ 21 ]. Our study seeks to fill this gap by covering a total of 10 academic fields and 250 sub-fields.…”
Section: Introductionmentioning
confidence: 99%